Studi Karakteristik Sifat Kimia Tanah Ultisol Pada Lahan Perkebunan Kelapa Sawit Rakyat Di Desa Sejotang Kecamatan Tayan Hilir Kabupaten Sanggau - Rinaldi Purba; Rita Hayati; Abdul Mujib Alhaddad (Jurnal Sains Pertanian Equator, 2019)
as agricultural land for the oil palm plantation sector is common so palm plantation  in west kalimantan are spread in several districts ,one of them is Tayan hilir Regency.            This Study aims to provide information to farmers about the characteristics and chemical and nutrient properties palm soil plantation in ultisol soil.            This research carried out in the palm plantation area in the sejotang Tayan Hilir District, Sanggau  Regency. The Analysis at the Laboratory of Chemistry and Soil Fertility, Faculty of Agriculture, University of Tanjungpura Pontianak. The research take 3 months, Starting from 16 April 2019  preparation to presentation of results.            Based on the results of the study, the soil reaction (pH) in the study site was classified as very  acidic. Textures in the study locations use code K (composite) that is K2, K3, K5 are clay texture class, K1 belongs to class of dusty clay texture and K4 is clay texture class. The Bulk density ranged from 1.06 to 1.55 gr / cm3. N-Total and C-Organic are classified as low to moderate, phosphorus and Potassium are very low to low, Ca, Mg and base saturation (KB) are very low, CEC is low and saturation of Al are very high. The level of soil fertility at the study site ask low.Keywords: Chemical Properties, Ultisols, Palm Oil.